Psychological capital and procrastination among mothers in higher education - Walter, Ofra; Hazan-Liran, Batel (Frontiers in Education, 2025)
IntroductionStudent mothers often face distinct challenges as they juggle academic demands and family responsibilities, which can negatively affect their academic performance. Psychological capital (PsyCap)—encompassing hope, efficacy, resilience, and optimism—has been shown to support positive academic outcomes. This study explores the role of PsyCap in academic adjustment, examining academic procrastination as a potential mediator, and comparing experiences of student mothers to those of non-mothers.MethodsA cross-sectional design was utilized, involving 216 students from Israeli higher education institutions (156 mothers, 60 non-mothers). Participants completed a demographic questionnaire, the Psychological Capital Questionnaire, the Academic Adjustment Questionnaire (AAQ), and the Academic Procrastination Questionnaire. Statistical analyses included correlational tests and mediation analysis.ResultsPsyCap was positively correlated with academic adjustment and negatively correlated with academic procrastination in both groups. No significant differences were found between mothers and non-mothers in levels of PsyCap, procrastination, or adjustment. Mediation analysis confirmed that academic procrastination significantly mediated the relationship between PsyCap and academic adjustment for both student mothers and non-mothers.DiscussionFindings underscore the protective role of PsyCap in academic contexts, suggesting that it enhances adjustment by reducing procrastination. The absence of group differences points to the universal relevance of PsyCap across diverse student populations. These insights highlight the importance of cultivating psychological strengths and developing institutional supports tailored to the needs of student mothers.